Análisis del comportamiento de los créditos y la morosidad en el sistema financiero en la región Loreto periodo 2018 – 2022 - Cardenas Rengifo, Piero Luis (2025)
The objective of the research was to determine the behavior of credits and delinquencies in the financial system in the Loreto region, period 2018-2022; The research is basic, with a quantitative approach at a descriptive and cross sectional level; The investigation concludes that credits in the Loreto region have grown year after year, in 2018 the balance of credits reached the sum of 2,324 million soles throughout the financial system and in the following years it has been 2,400, 2,452, 2,598 and 2,810 million in the year 2022. Regarding delinquency, the lowest amounts are in the years 2020 and 2021 with 171.6 million soles and 197.5 million soles; The other years are above 200 million soles; In terms of delinquency rates every year they exceed 7%.